Effect of metallurgical variables on the austenite stability in fatigued AISI 304 type steels. (November 2017) - Man, Jiří; Smaga, Marek; Kuběna, Ivo; Eifler, Dietmar; Polák, Jaroslav
Highlights: Structural stability of wrought AISI 304-type austenitic stainless steels during low-cycle fatigue. Effect of chemical banding on the mechanical destabilization of the steel structure. Distribution of DIM in various semi-product forms (bars vs. plates or sheets) in 3D. Impact of the initial state of steels (as received vs. additionally solution annealed) on the DIM formation. Usefulness of color etching for systematic detection of DIM within the whole volume of fatigued steels. Abstract: Low-cycle fatigue behavior, destabilization of austenite and emergence of deformation induced martensite (DIM) was investigated in wrought AISI 304 type (304, 304L, 348) austenitic stainless steels of diverse semi-product forms. The specimens fabricated from cylindrical bars, plates or thin sheets were cyclically strained with high strain amplitudes under total strain control in symmetrical push-pull at room and depressed temperatures to different stages of fatigue life. Quantitative and qualitative data on the formation, morphology and specific distribution of DIM in the volume of the material within the whole gauge part of the specimens are confronted with the respective cyclic stress-strain response and discussed in terms of characteristic chemical heterogeneity. This heterogeneity arises in the form of chemical banding due to the complex solidification behavior of AISI 304 type steels and its contemporary production route. Possible effect of additional solution treatment (various cooling rates due to quenching in different media) on DIM formation is discussed.